Conceptual and Methodological Considerations on Effort: An Interdisciplinary Approach - Jonas Radl; Luis Miller (American Behavioral Scientist, 2021)
This introduction to the special issue "Interdisciplinary Perspectives on Effort" highlights the relevance of effort as a research object and pinpoints the potential of various approaches to contribute to the advancement of knowledge on this multifaceted phenomenon. Addressing three dimensions of research—on the measurement, determinants, and consequences of effort—the article also gives an overview of the collection of articles in the special issue. In terms of measurement, we distinguish between self-reported individual characteristics related to effort, on the one hand, and behavioral measures of effort referring to task performance on the other. Concerning determinants, we review the ways in which studies find incentives, personality characteristics, and family background to affect individual effort provisions. Finally, when it comes to consequences, we discuss effort as a source of legitimate entitlement to rewards, speaking to normative theories of justice, and effort as a driver of socioeconomic achievement, referencing debates about the respective benefits of cognitive and noncognitive skills. In concluding, the article distills selected lessons learned for future research on effort.
Keywords: 330; effort; personality traits; noncognitive skills; social justice